Comparison of thyroid hormone levels by sex in adult dogs - Osorio, José Henry (2016)
The aim of this study was to establish reference values for serum levels of thyroid stimulating hormone (TSH) and free tetraiodothyronine (T4L) in adult dogs in the area of Caldas, Colombia, and possible differences due to sex. Blood samples were collected from 78 intact dogs after fasting (40 females and 38 males older than one year of age). The serum concentration of TSH and T4L levels were determined by enzymatic immunoassay using commercial kits. TSH values for females were 0.53 ± 0.96 μUI/ml (range: 0.02-4.54) and for males were 0.36 ± 0.27 μUI/ml (0.02-0.91). T4L values for females were 1.08 ± 0.40 ng/dl (0.52-2.09), and for males was 1.07 ± 0.39 ng/dl (0.5-2.18). None statistical difference was found between sexes for both TSH and T4L.